A Child’s Individuality of Mind as Depicted in Select-Short Stories of Ruskin Bond following the American Psychological Association’s Guidelines - Sharma, Paarull (International Journal of Psychosocial Rehabilitation, 2020)
This paper intends to explore the individuality of mind as visible in the child characters in the select short stories of Ruskin Bond. These seemingly ordinary characters possess extra-ordinary traits as they no longer view the world and situations as dictated by their elders; rather, they react to circumstances after logically judging them on their own. The ideology of these characters, despite their humble background and nonexistent contact with the fast-moving world, possesses a sense of maturity that puts them head and shoulders above their counterparts living in the luxurious environs. This paper is divided into three sections.